Corporate governance in Indonesia: One decade perspective - Aliffianti Safiria Ayu Ditta; Doddy Setiawan (University of Merdeka Malang, 2019)
This study aim in describing the development of research on corporate governance in Indonesia. The sample of the study consists of 101 articles from 10 Indonesian accredited journals at 2007-2017 periods. This research applies to chart the field method that classifies articles based on topic, disciplines and research methods. Most of the article (40 out of 101 articles) study the consequences of the emergence of corporate governance, such as the performance of the company and most of the article applies the analytical method (96 articles). However, the discussion on Indonesia institutional context, such as two-tier board systems, is still rare. The study mostly focuses on the monitoring function of the Board of Commissioners. Most of the study also investigated the effect of corporate governance practice on firm performance. Followed by the effect of corporate governance practice on disclosure. Further, most of the study conducted research on short periods (3.5 years). It is expected that this article provides a review of the recent development of corporate governance research in Indonesia and the opportunity to conduct the study.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v23i1.2182